A Case of Complex Partial Seizures Presenting as Acute and Transient Psychotic Disorder - Sadia Sultan; Ebtihaj Omar Fallata (Case Reports in Psychiatry)
Introduction. Complex partial seizures are focal (CPS) (i.e., start in one area of the brain) and associated with impairment in consciousness. Most of them arise in the temporal region and are characterized by aura, impaired consciousness, and automatisms. CPS that arise in temporal region are most often misdiagnosed as primary psychiatric illness. Case Report. A 25-year-old male presented with fluctuations in consciousness, aggressive behaviour, hallucination, and delusions of grandeur lasting a few hours. He was diagnosed with acute and transient psychotic disorder according to ICD10 criteria and was treated with intramuscular haloperidol 10mg BID followed by oral olanzapine 10mg. Computed tomography of brain and electroencephalogram were normal. After 15 days he presented again to the outpatient department with complaints of aggressive behaviour and sensory misinterpretations. Video electroencephalogram was recommended, which was not done due to financial constraints. The diagnosis was reconsidered and he was started on oral carbamazepine due to high clinical suspicion, of complex partial seizures, in spite of lack of EEG evidence. He responded well to antiepileptic and symptom remission has maintained well. Conclusion. Patients presenting with psychosis need careful diagnostic evaluation for other possibilities.